A qualitative study of the IPS employment specialist role in the context of Nav employment in Norway - Cathrine Moe; Beate Brinchmann; Unni Kolstad; Kristine Steen; David McDaid; Eoin Killackey; Miles Rinaldi; Marit Borg; Arnstein Mykletun (BMC Psychiatry)
Abstract Background Employment is recognised as a fundamental human right. Still, many people experiencing severe mental illness are outside the workforce. Appropriate employment has several benefits for mental health and is central to recovery and citizenship. Individual Placement and Support (IPS) integrates treatment and employment support and is an evidence-based model for supporting people experiencing severe mental illness to gain and maintain employment. Employment specialists are front-line workers of IPS. In Norway, the implementation of IPS is in a later phase and employment specialists are employed outside health services. This study explores and describes employment specialists’ job situation within this new context. Methods Qualitative data were collected through field notes and five focus group interviews. The study participants were 36 IPS employment specialists located at 13 different sites in Northern Norway. Transcripts and field notes were analysed by thematic analyses. Results Our findings show that the IPS structures are settled in Norway, but some challenges remain. The most prominent consequence of the new context is the challenge of integration within health teams. Nonetheless, employment specialists find their work with clients meaningful and having great impact with opportunities for personal and professional development. Conclusion IPS is anchored in Norwegian policy and several of the early intervention challenges are resolved. Our study provides increased understanding of the employment specialists job situation within the new IPS context in Norway. Employment specialists are “front-line-workers” in enacting the IPS principles, and their perspectives on the contextual change are crucial in the development of IPS.